2009
DOI: 10.1016/j.otohns.2009.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a tongue‐holding maneuver during swallowing evaluated by high‐resolution manometry

Abstract: Aim: This study aimed to investigate the effects of tongue-holding maneuver (THM) during swallowing using a novel high-resolution manometry (HRM) system. Materials and Methods: Thirty three asymptomatic Japanese adults were studied. A solid-state HRM assembly with 36 circumferential sensors spaced 1 cm apart was positioned to record pressures from the velopharynx to the upper esophagus at rest and during swallowing. The maximum values of the dry swallowing pressures at velopharynx, meso-hypopharynx, upper esop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 15 publications
(36 reference statements)
0
29
1
6
Order By: Relevance
“…Previous reports have combined pressures from the tongue base and hypopharynx in a single region (18, 19, 24). For the purposes of this study, we have separated these pressures into two regions, based on the shapes of the pressure waves.…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports have combined pressures from the tongue base and hypopharynx in a single region (18, 19, 24). For the purposes of this study, we have separated these pressures into two regions, based on the shapes of the pressure waves.…”
Section: Methodsmentioning
confidence: 99%
“…Die Ösophagushochauflösungsmanome-trie (öHRM) unterscheidet sich von der herkömmlichen Ösophagusmanomet-rie insbesondere durch die Anzahl, Verteilung und Platzierung der Sensoren [21,26]. [21,27].…”
Section: öSophagushochauf-lösungsmanometrieunclassified
“…Nach einem Nullabgleich wurde der Katheter transnasal eingeführt und mit einem Pflaster an der Nase befestigt. Echtzeitabbildungen des Drucks unterstützten die exakte Platzierung, da das Hochdruckareal des oÖS in Ruhe einfach identifizierbar ist [26,29,30]. Der Katheter wurde so weit eingeführt, dass der oÖS im Bereich der Sensoren P5-P9 dargestellt wurde.…”
Section: Messprozedereunclassified
“…More recently, high-res-olution impedance manometry (HRIM) has been introduced; this technique combines the benefits of HRM and impedancebased bolus transit assessments. Several studies have reported the utility of high-resolution impedance manometry (HRIM) in the evaluation of OPD (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%